PENGARUH LITERASI HALAL, RELIGIOSITAS, DAN KEPATUHAN HUKUM TERHADAP MOTIVASI PENGAJUAN SERTIFIKASI PRODUK HALAL PELAKU UMKM PANGAN DI KOTA DEPOK - Zamira Adia Aprimarianti (2022)
The enactment of regulations regarding the obligation to guarantee halal products in Indonesia according to Law NO 33 of 2014 requires MSME actors to have halal guarantees for the products they sell. However, the number of Indonesian MSMEs that have been halal certified is still very low. The purpose of this study was to analyze the effect of the level of literacy, religiosity, and obidience law of UMKM players in Depok City on halal product guarantee regulations using a quantitative approach with a research instrument in the form of a questionnaire and distributed to MSME players in Depok City. Sampling in this study used a purposive sampling technique and obtained as many as 152 food SMEs in Depok City who had not been halal certified. The results of this study are that halal literacy and religiosity have an influence on the motivation of MSMEs to apply for halal certification. Obidience law has no effect on the motivation to apply for halal product certification among MSMEs in Depok City. The results of this study are expected to have a contribution to the implementation of halal certification policies and the growth of the halal industry in Indonesia.